MODEL KELEMBAGAAN KELOMPOK TANI PADA SISTEM INTEGRASI TANAMAN DAN TERNAK DI KABUPATEN GROBOGAN - Cahyati Setiani; Teguh Prasetyo (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2003)
One of crucial factor in application for Low External Input Sustainable Agricultural(LEISA) model by crop-livestock integration system is institutional performance. Study on the insti• tutional performance of farmer group in crop-livestock integration system was conducted in Grobogan Regency in 2000-2002. The study was conducted by survey method with Europe Foundation Quality Management (EFQM) approach. This study aims to get an alternative model of farmer group which can apply LEISA. Institution engineering is done by perfecting organitation structure and managementtraining. Institutional orientation is directedto economy aspect, especially in exploring local resourcecontinously and non farmingactivity. The training is directed to Total Quality Management (TQM) application in managing farmer group institution. On the whole, crop-livestock integration technology wich is structured can decrease external cost and increase the farmer income. The institutional performance of farmer group get 6,06% achievement in 2001 and increase to 12,3% in 2002. Although these performance is long enough for excellent level (50%), there is indication that institution engineering of farmer group which is applied support LEISA grateful and farmer's income upgrading continously.